First report on the leafhopper genus Takama Dworakowska & Viraktamath (Hemiptera: Cicadellidae: Typhlocybinae) from Hainan Island, China, with the description of two new species - Song, Yuehua; Li, Zizhong (Zootaxa, 2011)
The leafhopper genus Takama Dworakowska & Viraktamath (1975) is reported for the first time from China. In the present paper, two new species, Takama horna sp. nov., Takama jianfenga sp. nov. from Hainan Island, China are described and illustrated.